Optimal conditions for assay of haemolytic component of camel complement in classical pathway - CHOPRA, V; KASHYAP, S K (The Indian Journal of Animal Sciences, 2014)
Haemolytic complement of camel serum was assayed under standardized conditions. CH50 titres in the range of 110.03-417.8 units ml-1 of camel serum with a mean of 197.8 were obtained. Effect of various variables on the lytic activity of camel complement in classical pathway was studied. The standard system of titrating the HC level consisted of rabbit erythrocytes sensitized with goat haemolysin as indicator system, veronal buffer saline, pH 7.3, ionic strength 0.15M, Ca2+ and Mg2+ concentrations of 4.10-4 and 1.10-3M, respectively. Incubation at 37Â°C for 60 min gave the highest HC activity. Higher Na2 EDT A concentrations than 5.10-4 M inhibited haemolytic activity to undetectable levels.